2011
DOI: 10.1016/j.febslet.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Silencing activity of 2′-O-methyl modified anti-MDR1 siRNAs with mismatches in the central part of the duplexes

Abstract: Edited by Tamas DalmayKeywords: RNA interference siRNA Thermodynamic stability MDR1 2 0 -O-Methyl modification a b s t r a c tThe thermodynamic properties of siRNA duplexes are important for their silencing activity. siRNAs with high thermodynamic stability of both the central part of the duplex and in the whole, usually display low silencing activity. Destabilization of the central part of the siRNA duplex could increase its silencing activity. However, mismatches located in the central part of the duplex cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…These are degradation of siRNA by serum nucleases, binding of siRNA with serum protein, siRNA accumulation in non-target organs and tissues, excretion by the kidneys, low bioavailability, and inefficient silencing within the cells 11 . To study the performance of anti- MDR1 siRNA and its conjugate with cholesterol in vivo, we chose siRNA targeted to the 411–431 nt region of human MDR1 mRNA (siMDR), shown in our previous study to have the highest bioactivity in cell culture 25 . 2′-O-methyl modifications were introduced into nuclease-sensitive sites according to the algorithm developed by us previously 23 .…”
Section: Resultsmentioning
confidence: 99%
“…These are degradation of siRNA by serum nucleases, binding of siRNA with serum protein, siRNA accumulation in non-target organs and tissues, excretion by the kidneys, low bioavailability, and inefficient silencing within the cells 11 . To study the performance of anti- MDR1 siRNA and its conjugate with cholesterol in vivo, we chose siRNA targeted to the 411–431 nt region of human MDR1 mRNA (siMDR), shown in our previous study to have the highest bioactivity in cell culture 25 . 2′-O-methyl modifications were introduced into nuclease-sensitive sites according to the algorithm developed by us previously 23 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2010 Maier and co-workers reported that the modulation of the thermal stability can enhance the potency of siRNA molecules [39]. The destabilization of the siRNA duplex could be achieved by the introduction of chemical modifications or on account of base pair mismatches [40,41]. The melting data stressed the destabilizing effects of the T L presence on the siRNA duplex (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…4 and 6 days post‐transfection, the culture medium was removed and the cells were lysed in 60 μl of Sample buffer (Sigma–Aldrich, USA). Western blotting was performed as described with [12] (detailed information in Supplementary material).…”
Section: Methodsmentioning
confidence: 99%